92 THE RISE OF SIMULATION BASED TRAINING IN GERIATRIC MEDICINE?. (18th November 2021) - Buckley, E; O'Regan, N; Pope, G; Mulcahy, R; Cooke, J
Abstract: Background: Simulation-based training (SBT) offers opportunities for teaching and learning in safe spaces, while learners navigate the acquisition of these complex skills, and work in clinically-realistic teams, supported by faculty. Geriatric medicine is a diverse speciality, requiring trainees to navigate complex social, medical, and ethical issues, necessitating a multifaceted and interdisciplinary approach. Studies describing SBT in geriatric medicine are limited. Methods: We hosted an in-situ competition designed to encourage participation in simulation and to develop a simulation faculty network across a hospital group. All healthcare professionals in the hospital group were eligible to enter. Contestants designed a simulation case scenario within a speciality of their choice. Entrants participated in five virtual workshops on core elements of SBT. Six cases were selected to participate in the virtual final. The finalists submitted a video summarising the performance of and evaluation of the learners' experience of the scenario. Results: Thirty-four teams submitted initial SBT proposals and participated in the five virtual SBT workshops over a three-week period. Of these, 17.6% (n = 6) were geriatric medicine teams, comprising seven geriatric medicine consultants, four advanced nurse practitioners and 13 non-consultant hospital doctors (five registrars, six senior house officers and two interns). Case scenarios submitted by geriatric medicine teams included acute stroke care, diagnosis and management of delirium, management of perioperative delirium post hip fracture and capacity assessment. Conclusion: The level of interest in SBT generated amongst geriatric medicine faculty and trainees suggests this may be a useful tool to enhance the training experience. SBT offers geriatric medicine trainees the opportunity to practice the technical and non-technical skills required to navigate complex, interdisciplinary and challenging patient scenarios, in a protected environment. In this innovation, we identified a range of geriatric medicine-related topics for which SBT was deemed to be valuable by both faculty and trainees and could be facilitated through in-situ simulation settings.